A re-examination of the taxonomic status of Prostoma jenningsi—a Freshwater Nemertean - Quigg, Siobhan Marie; Lowe, Christopher Nathan; Butt, Kevin Richard; Mitcham, Timothy; Iyengar, Arati (Zootaxa, 2020)
Prostoma jenningsi was first recorded at the Clay ‘Ole pond in Lancashire, UK, in 1969 and was distinguished histologically from other Prostoma by the presence of 11 proboscidial nerves (with all other Prostoma species thought to have 9-10). P. jenningsi was considered to be the only species endemic to Lancashire and listed in the British Red Data Book as ‘Insufficiently Known’ as well as a ‘Species of Principal Importance’ under the UK Natural Environment and Rural Communities Act (2006).                A limited number of Prostoma spp were recovered from the Clay ‘Ole in 2011 (the first confirmation of the presence of Prostoma spp. since 1999). In 2015, further sampling was undertaken and expanded to other ponds in Lancashire resulting in the discovery of Prostoma spp. at a further 3 locations. Thereafter, DNA sequencing of nuclear 18S ribosomal RNA and mitochondrial Cytochrome Oxidase I (COI) genes were undertaken and phylogenetic analyses performed to establish the taxonomic status of recovered specimens. All available Prostoma sequences (Prostoma eilhardi and Prostoma graecense) were downloaded from GenBank® and Barcode of Life Data System (BOLD) databases for comparison.                All 18S sequences from samples in Lancashire were identical to each other and to all downloaded Prostoma sequences, allowing no further analyses. With COI, 50 individuals were collected from 4 locations across Lancashire and sequenced, comparing a total of 480 base pairs. Average uncorrected p-distances between UK and European samples were low, although some more geographically distant samples from California, USA, displayed higher uncorrected p-distance values.                Results suggest that the Prostoma recovered from the Clay ‘Ole (and all other sampled locations in Lancashire) are not distinct from P. eilhardi and P. graecense (as downloaded from GenBank® and BOLD) suggesting that there is a strong case for the species status of P. jenningsi to be revoked. Further regional and national sampling is required to obtain a clearer evaluation of the distribution of Prostoma and the levels of genetic diversity present in the UK. In addition, results from this study indicate that thorough taxonomical re-evaluation of species within the Prostoma genus is required.